Accidental Genetic Engineers: Horizontal Sequence Transfer from Parasitoid Wasps to Their Lepidopteran Hosts - Schneider, Sean E.; Thomas, James H. (PLOS ONE, 2014)
We show here that 105 regions in two Lepidoptera genomes appear to derive from horizontally transferred wasp DNA. We experimentally verified the presence of two of these sequences in a diverse set of silkworm (Bombyx mori) genomes. We hypothesize that these horizontal transfers are made possible by the unusual strategy many parasitoid wasps employ of injecting hosts with endosymbiotic polydnaviruses to minimize the host's defense response. Because these virus-like particles deliver wasp DNA to the cells of the host, there has been much interest in whether genetic information can be permanently transferred from the wasp to the host. Two transferred sequences code for a BEN domain, known to be associated with polydnaviruses and transcriptional regulation. These findings represent the first documented cases of horizontal transfer of genes between two organisms by a polydnavirus. This presents an interesting evolutionary paradigm in which host species can acquire new sequences from parasitoid wasps that attack them. Hymenoptera and Lepidoptera diverged ∼300 MYA, making this type of event a source of novel sequences for recipient species. Unlike many other cases of horizontal transfer between two eukaryote species, these sequence transfers can be explained without the need to invoke the sequences ‘hitchhiking’ on a third organism (e.g. retrovirus) capable of independent reproduction. The cellular machinery necessary for the transfer is contained entirely in the wasp genome. The work presented here is the first such discovery of what is likely to be a broader phenomenon among species affected by these wasps.